Sustenance and performance: nutritional reserves, longevity and contest outcomes of fed and starved adult parasitoid wasps - Snart, Charles J.P.; Kapranas, Apostolos; Williams, Huw; Barrett, David A.; Hardy, Ian C. (Frontiers Media, 2018)
Dyadic contests for possession of resources occur across a wide range of animal taxa, with contest outcome often being heavily influenced by the energetic reserves of the competitors. The majority of studied parasitoid wasps lack de novo lipogenesis, with adult lipid reserves being limited to those acquired throughout larval development. Carbohydrate- and lipid-rich adult diets can increase adult parasitoid lifespan and fecundity by potentially acting as a maintenance energy store. However, the effects of such diets on fat reserve compositions and some aspects of parasitoid behaviour contest outcome dynamics have not been examined. This study assesses the effect of a carbohydrate rich diet (honey) on the longevity, metabolic state and contest performance of Goniozus legneri, a bethylid wasp. The longevity of honey-fed diet adults was typically more than twice that of starved wasps. Compared to similarly-aged starved wasps, honey feeding increased concentrations of common haemolymph sugars and amino acids in a 3-day old and 7-day old wasps, and higher concentrations of stored lipid in7-day old wasps. However, nutritional status did not affect the outcome of dyadic contests over host possession when both contestants were either 3 days or 7 days old. While contest dynamics outcome may be unaffected by diet, it remains possible that an enhancing effect of feeding on contest ability is matched by an effect of higher value being placed on winning by starved wasps.